2004
DOI: 10.1081/ese-120027724
|View full text |Cite
|
Sign up to set email alerts
|

Elemental and Ionic Concentrations in the Urban Aerosol in Antwerp, Belgium

Abstract: The results of a study of the elemental and ionic composition of the ambient aerosol in and around Antwerp are presented. Four sampling campaigns were performed, covering all seasons. The samples were obtained by filtration and impaction methods. Subsequently, the filters were analyzed by X-ray fluorescence spectrometry for elements, and the impactor substrates were leached with water and analyzed by ion chromatography for ions. When comparing the results of the chemical analysis with the meteorological inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, Na þ and K þ the only species to display three modes with the intermediate mode at around 1 mm not corresponding to an anion analysed here. It is possible that this is an indication that the marine and terrestrial borne particles have two distinct coarse modes as indicated by other studies elsewhere bothe for crustal elements (Eleftheriadis and Colbeck, 2001) and ionic species (Deutsch et al, 2004). On the other hand an intermediate mode for K þ was observed also in background aerosol and may originate from biomass burning.…”
Section: àmentioning
confidence: 77%
“…However, Na þ and K þ the only species to display three modes with the intermediate mode at around 1 mm not corresponding to an anion analysed here. It is possible that this is an indication that the marine and terrestrial borne particles have two distinct coarse modes as indicated by other studies elsewhere bothe for crustal elements (Eleftheriadis and Colbeck, 2001) and ionic species (Deutsch et al, 2004). On the other hand an intermediate mode for K þ was observed also in background aerosol and may originate from biomass burning.…”
Section: àmentioning
confidence: 77%
“…Numerous researchers apply XRF to analyze aerosols collected in different locations in order to estimate the level of air pollution. About 50-100 articles have been published annually, over the last two decades, on X-ray emission spectrometry for aerosol analysis, e.g., Marcazzan et al, 1,2 Injuk et al, 3 Samek et al, 4 and Deutsch et al 5 used the energydispersive (ED) mode of XRF. Conventional EDXRF has the advantages of moderate cost and the possibility of determining simultaneously a wide range of elements, as well as the possibility of automatic running; no dissolution step is required prior to analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of sampling strategy has been a recurring theme throughout this review period for investigations into elemental characterisation and the mobility of airborne particulates. Deutsch et al 290 used filtration and impaction methods to collect samples representing all four seasons of the year. They found that element concentrations were affected by both the location of the sampling site and meteorological conditions, as only heavy rains were able to provide sufficient removal of the aerosols from the atmosphere.…”
Section: Geological and Industrial Mineralsmentioning
confidence: 99%